2012
DOI: 10.1038/jid.2011.260
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma and Merkel Cell Polyomavirus: Evidence for Hit-and-Run Oncogenesis

Abstract: IKK-gamma protein is a target of BAG3 regulatory activity in human tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…An alternative explanation for RB1 mutation in Merkel cell carcinoma might include the proposed model of hit-and-run oncogenesis in which Merkel cell polyomavirus integrates in to the host genome of all Merkel cell carcinoma cases, does genetic damage, either persists as clonally integrated virus or is expelled from the human genome by various repair mechanisms. 51 Integrating our data with this model, Merkel cell polyomavirus may initiate Merkel cell carcinoma tumorogenesis in a subset of cases, including a genetic 'hit' to RB1 such as nonsense truncating mutations. After this 'hit' occurs, Merkel cell polyomavirus is no longer necessary for Merkel cell carcinoma progression and maintenance and the virus leaves ('runs' from) the human host genome.…”
Section: Modern Pathology (2014) 27 1073-1087mentioning
confidence: 70%
“…An alternative explanation for RB1 mutation in Merkel cell carcinoma might include the proposed model of hit-and-run oncogenesis in which Merkel cell polyomavirus integrates in to the host genome of all Merkel cell carcinoma cases, does genetic damage, either persists as clonally integrated virus or is expelled from the human genome by various repair mechanisms. 51 Integrating our data with this model, Merkel cell polyomavirus may initiate Merkel cell carcinoma tumorogenesis in a subset of cases, including a genetic 'hit' to RB1 such as nonsense truncating mutations. After this 'hit' occurs, Merkel cell polyomavirus is no longer necessary for Merkel cell carcinoma progression and maintenance and the virus leaves ('runs' from) the human host genome.…”
Section: Modern Pathology (2014) 27 1073-1087mentioning
confidence: 70%
“…In our analysis we could detect virus-T integration in 36% of the virus positive patients (total 83%) and the highest number of these integrations was detected in stage III/IV patients with progressive disease. The fact that only a portion, but not all of the positive patients display integrated virus, may be supported by the proposed hit-and-run oncogenesis model [10]. According to this hypothetical working model, the virus may be present for the initial transformation, but once into the cells, and after inducing genetic damages, it is either integrated in the genome or is released from cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although MCPyV was found ubiquitously throughout the population, we and others have shown that viral DNA was integrated in the genome of MCC but not in other skin tumours [7][8][9]. However, a correlation between MCPyV positivity of MCC and survival rate of affected patients is still controversially discussed [10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…Although, Houben et al (2011) presented results that the MCC MCV-positive lineage Loke did not subside even with the silencing of viral T antigens. Thus, it was suggested that MCV operates only in the early carcinogenic process in some MCC cases, and that the loss of MCV after this step may take the cancer to a more aggressive behavior [76,96].…”
Section: Possible Carcinogenic Mechanisms Of MCVmentioning
confidence: 99%